New insights into the stability of alkenes and alkynes, fluoro-substituted or not: a DFT, G4, QTAIM and GVB study - Freitas, Gutto Raffyson Silva de (2020)
Many undergraduate organic chemistry books do not agree with the order of relative stability of alkenes towards hydrogenation reactions. Although they ascribe the stability of alkenes to the number and spatial position of the alkyl groups attached to the vinyl carbon atoms, results from the quantum theory of atoms in molecules indicate that the influence of an alkyl substituent on the stability of unsaturated hydrocarbons arises from the slight removal of electron density of the π bond, not from donation of their charge density to unsaturated carbon atoms as stated in many text books. There is an inverse relation between delocalization index—the number of shared electrons between two atoms, or Wiberg bond index of C=C bond—and the number of methyl groups attached to the vinyl carbon atoms. Electron withdrawing groups (EWGs) attached to unsaturated carbon atoms of alkenes and alkynes have two different behaviors: slight EWGs (alkyl groups) stabilize unsaturated carbon atoms while the strong EWG destabilizes the unsaturated carbon atoms. Generalized valence bond theory was also used to study the ambiguous behavior of fluorine substituents bonded to vinyl carbon atoms.